Small-angle X-ray scattering and structural modeling of full-length: Cellobiohydrolase I from Trichoderma harzianum - Lima, Leonardo H.F.; Serpa, Viviane I.; Rosseto, Flávio R.; Sartori, Geraldo Rodrigues; de Oliveira Neto, Mario [UNESP]; Martínez, Leandro; Polikarpov, Igor (Springer Nature, 2013)
Cellobiohydrolases hydrolyze cellulose releasing cellobiose units. They are very important for a number of biotechnological applications, such as, for example, production of cellulosic ethanol and cotton fiber processing. The Trichoderma cellobiohydrolase I (CBH1 or Cel7A) is an industrially important exocellulase. It exhibits a typical two domain architecture, with a small C-terminal cellulose-binding domain and a large N-terminal catalytic core domain, connected by an O-glycosylated linker peptide. The mechanism by which the linker mediates the concerted action of the two domains remains a conundrum. Here, we probe the protein shape and domain organization of the CBH1 of Trichoderma harzianum (ThCel7A) by small angle X-ray scattering (SAXS) and structural modeling. Our SAXS data shows that ThCel7A linker is partially-extended in solution. Structural modeling suggests that this linker conformation is stabilized by inter- and intra-molecular interactions involving the linker peptide and its O-glycosylations. © 2013 Springer Science+Business Media Dordrecht.
Keywords: CBH1; Cellobiohydrolase; Cellulose; Trichoderma; Biotechnological applications; Cellobiohydrolases; Cellulose-binding domain; Intramolecular interactions; Small angle X-ray scattering; Two-domain architecture; Cellulosic ethanol; Molecular structure; Peptides; X ray scattering